The Influence of Gratitude toward Psychological Resilience of Adolescence Living in Youth Social Care Institution - Listiyandini, Ratih Arruum (Journal of Educational, Health and Community Psychology, 2018)
Â This study aims to determine the role of gratitude towards psychological resilience of adolescents who live in youth social care institutions (orphanages). The study was conducted using a quantitative approach and cross-sectional design. The population of the study was adolescents who lived at youth social care institutions in Jakarta and Bekasi. Two hundred samples were obtained by convenience sampling. The researcher used the Indonesian version of the gratitude scale and the adaptation of resilience scale as measurement tools. Regression analysis found that gratitude explains 13.1 percent variance of adolescencesâ psychological resilience. The role of gratitude toward psychological resilience is positive, which is higher gratitude will also be followed by higher resilience. Therefore, gratitude needs to be considered in the development of resilience program for adolescents living in youth social care institutions.Â